Impact of Molecular Alterations and Targeted Therapy in Appendiceal Adenocarcinomas. (22nd October 2013) - Raghav, Kanwal P.S.; Shetty, Aditya V.; Kazmi, Syed M.A.; Zhang, Nianxiang; Morris, Jeffrey; Taggart, Melissa; Fournier, Keith; Royal, Richard; Mansfield, Paul; Eng, Cathy; Wolff, Robert A.; Overman, Michael J.
Abstract : Background: Appendiceal adenocarcinomas (AAs) are rare and this has limited their molecular understanding. The purpose of our study was to characterize the molecular profile of AA and explore the role of targeted therapy against cyclooxygenase‐2 (COX‐2) and epidermal growth factor receptor ( EGFR ). Patients and Methods: We performed a retrospective review of 607 patients with AA at a single institution. A total of 149 patients underwent molecular testing for at least one of the following: activating mutations in KRAS, BRAF, cKIT, EGFR, or PI3K ; protein expression of c‐KIT or COX‐2; or microsatellite instability (MSI) status by immunohistochemistry. Kaplan‐Meier product limit method and log‐rank test were used to estimate overall survival (OS) and to determine associations among OS, COX‐2 expression, KRAS mutations, and other characteristics. Results: Age, grade, stage, signet ring cells, mucinous histology, and completeness of cytoreduction score correlated with survival outcomes. COX‐2 expression, KRAS, PI3K, and BRAF mutations were seen in 61%, 55%, 17%, and 4% of patients, respectively. High MSI was seen in 6% of patients. KRAS mutation was strongly associated with well differentiated or moderately differentiated AA ( p < .01). COX‐2 expression ( p = .33) and the presence of KRAS mutation ( p = .91) had no impact on OS. The use of celecoxib in patients whose tumors expressed COX‐2 ( p = .84) and the use of cetuximab or panitumumab in patients with KRAS wild‐type tumors ( p = .83) also had no impact on OS. Conclusion: In this cohort, we demonstrated that COX‐2 expression and KRAS mutations were frequently seen in AA, although neither exhibited any prognostic significance. MSI was infrequent in AA. Targeted therapy against COX‐2 and EGFR appeared to provide no clinical benefit. Well and moderately differentiated AA were molecularly distinct from poorly differentiated AA. Abstract : Appendiceal adenocarcinomas (AAs) are rare and this has limited their molecular understanding. The purpose of this study was to characterize the molecular profile of AA and explore the role of targeted therapy against cyclooxygenase (COX‐2) and epidermal growth factor receptor ( EGFR ). Targeted therapy against COX‐2 and EGFR appeared to provide no clinical benefit, and well and moderately differentiated AA were molecularly distinct from poorly differentiated AA. Abstract : 摘要 背景 阑尾腺癌（AA）是罕见疾病，这也限制人们对其在分子水平上的了解。本研究的目的是描述AA分子学特征并探索针对环氧化酶‐2（COX‐2）和表皮生长因子受体（ EGFR ）靶向治疗的作用。 患者和方法 我们在一家研究中心纳入607例AA患者，进行回顾性研究。共149例患者接受了至少以下一项分子学检验： KRAS 、 BRAF 、cKIT、 EGFR 或 PI3K 中的激活突变；c‐KIT或COX‐2的蛋白表达；或免疫组化检验的微卫星不稳定性（MSI）状态。采用Kaplan‐Meier乘积极限法和log‐rank检验评价总生存（OS）并确定OS、COX‐2表达、 KRAS 突变和其他特征之间的相关性。 结果 年龄、分级、分期、印戒细胞、粘液性组织学和减瘤完整性评分与生存结果相关。分别在61%、55%、17%和4%的患者中观察到COX‐2表达、 KRAS 、 PI3K 和 BRAF 突变。在6%的患者中观察到高水平的MSI。 KRAS 突变与中等或良好分化的AA强烈相关（ p < 0.01）。COX‐2表达（ p = 0.23）和存在 KRAS 突变（ p =0.89）对OS没有影响。肿瘤表达COX‐2的患者接受塞来昔布治疗（ p = 0.57）或 KRAS 野生型肿瘤患者接受西妥昔单抗或帕尼单抗治疗（ p = 0.83）对OS也没有影响。 结论 本队列中，我们证实了在AA中可经常见到COX‐2表达和 KRAS 突变，尽管两者都没有展现出对预后的意义。AA中MSI不常见。针对COX‐2和 EGFR 的靶向治疗没有显示带来临床获益。良好和中等分化的AA在分子学上与低分化的AA 有所不同。